2021
DOI: 10.1111/brv.12815
|View full text |Cite
|
Sign up to set email alerts
|

Group I PAKs in myelin formation and repair of the central nervous system: what, when, and how

Abstract: p21‐activated kinases (PAKs) are a family of cell division control protein 42/ras‐related C3 botulinum toxin substrate 1 (Cdc42/Rac1)‐activated serine/threonine kinases. Group I PAKs (PAK1–3) have distinct activation mechanisms from group II PAKs (PAK4–6) and are the focus of this review. In transformed cancer cells, PAKs regulate a variety of cellular processes and molecular pathways which are also important for myelin formation and repair in the central nervous system (CNS). De novo mutations in group I PAKs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 179 publications
0
24
0
Order By: Relevance
“…7). Even though we could not exclude that the observed effects of NVS could be related to PAK1 inhibition in neurons and other glial cells (25,26), our results indicate that sustained inhibition of PAK1 activity in OLs promotes myelination ex vivo.…”
Section: Pak1 Inhibition Increases Myelin Membrane Expansion and Myel...mentioning
confidence: 70%
See 1 more Smart Citation
“…7). Even though we could not exclude that the observed effects of NVS could be related to PAK1 inhibition in neurons and other glial cells (25,26), our results indicate that sustained inhibition of PAK1 activity in OLs promotes myelination ex vivo.…”
Section: Pak1 Inhibition Increases Myelin Membrane Expansion and Myel...mentioning
confidence: 70%
“…We previously showed that PAK3 is highly expressed in OPCs but weakly expressed in OLs and that PAK3 is involved in OPC differentiation (29). Conversely, transcriptome and protein expression analyses have shown that PAK1 is highly expressed in OLs compared to OPCs (26,(30)(31)(32), suggesting that PAK1 may be a relevant candidate for controlling myelin membrane expansion, hence sheath wrapping around axons.…”
Section: Introductionmentioning
confidence: 99%
“…PAK3 is mostly expressed in the brain, with a particularly strong expression in the hippocampus. At the cellular level in the brain, PAK1 is found only in neural lineage cells, PAK2 is expressed in every cell types and PAK3 can be found in neurons as well as oligodendrocyte progenitor cells (Figure 5A; Zhang et al, 2014;Maglorius Renkilaraj et al, 2017;Magne et al, 2021;Wang and Guo, 2022). However, some differences were noticed in PAK expression between mouse and human brain (Figure 5A; Civiero and Greggio, 2018;Zhang K. et al, 2022).…”
Section: Pak Expression Patterns and Mutation Pathogenicitymentioning
confidence: 97%
“…Group I PAKs includes PAK1, 2 and 3; group II includes PAK4, 5 and 6 which have not been associated with NDDs yet (Jaffer and Chernoff, 2002;Bokoch, 2003). Several reviews describe the biological functions of PAKs in cell signaling and neuronal pathophysiology (Bokoch, 2003;Kreis and Barnier, 2009;Koth et al, 2014;Kumar and Li, 2016;Civiero and Greggio, 2018;Wang and Guo, 2022;Zhang K. et al, 2022). Functions of group I PAKs are similar in a broad way because of their high sequence identity, their common modes of regulation as well as the substrates they share.…”
Section: Introductionmentioning
confidence: 99%
“…Pak1 is an essential Rac1 downstream protein, and research suggests that Rac1/Pak1 signalling pathway plays a signi cant role in healing nervous system injuries [27]. However, the downstream signalling pathway of Rac1/Pak1 in nerve injury repair remains unclear.…”
Section: The Rac1/ Pak1/p38 Signalling Pathway Is Enhanced In Respons...mentioning
confidence: 99%